Analisis Resepsi Agen Asuransi Mengenai Gambaran Kerja Keras dalam Video Klip Ardhito Pramono ‘925’ - Alya Jordania; Syaifuddin (UNIVERSITAS KALBIS, 2022)
Hard work has a correlation with work completion and overcoming various obstacles. This also appeared in Ardhito Pramono's video clip titled